Bioactive potential and storage behavior of low molecular mass peptides in Pilsner and IPA style craft beers - Roberta Nogueira Pereira da Silva; Angelica Priscila Parussolo Tonin; Gabriela Soares Macello Ramos; Juliana Furtado Dias; Eduardo Cesar Meurer; Maria Gabriela Bello Koblitz (Frontiers in Food Science and Technology)
Beer, one of the most widely consumed alcoholic beverages globally, is typically produced from barley and hops, and contains carbohydrates, proteins, vitamins, minerals, ethanol, and bioactive phytochemicals such as phenolic compounds. However, the knowledge of protein content, particularly bioactive peptides in beer, remains limited. Given that beer production involves raw materials rich in both proteins and proteolytic enzymes, which may remain active throughout the product’s shelf life, beer holds potential as a source of bioactive peptides. This study aimed to investigate the presence of bioactive di- and tripeptides in craft beer samples from Pilsner and IPA styles, after 3 or 6 months of storage. LC-MS/MS analysis was performed using the 46 Da neutral loss method and collision-induced dissociation, followed by peptide bioactivity screening through the BIOPEP database. Twelve di- and tripeptides, with masses ranging from 177 to 329 (m/z), were identified, exhibiting potential bioactivities such as dipeptidyl peptidase IV and III inhibition, ACE inhibition, and antioxidative properties. These activities are associated with reduced risk of high blood pressure and metabolic syndrome. After 3 months of storage, peptide intensity decreased in Pilsner samples but increased in IPA samples. Pilsner beers, typically clear due to added chill-proofing proteases, showed reduced peptide intensity over time, whereas IPA, which often remains hazy and lacks such enzymes, exhibited increased peptide levels. These findings suggest that Pilsner beers may benefit from quicker consumption, while IPA may be better suited for longer storage to maximize bioactive peptide intake.